Development of A QR Code-Based Attendance System for Factory Employees - Nuralif, Ikhwan; Fachrie, Muhammad (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
Employees are the most asset for any company. Achieving the best results from employees should be accompanied by a comfortable working environment. Whether working in an office or in the field, attendance is of utmost importance. Attendance is a crucial factor that can support and motivate every work activity. In this advanced era, many companies still rely on manual attendance systems. The use of manual systems often leads to errors caused by both administrators and employees, such as inefficient paper usage, failure to report absences, delayed submission of monthly reports, or loss of paper records. These issues can lead to employee carelessness, as there is a risk of attendance manipulation with manual (paper-based) attendance systems, resulting in attendance data falsification. By implementing QR codes, employees only need to scan the code using their smartphones. This research employs Unified Modeling Language (UML) for modeling. The application is then developed using Kodular and Firebase. The purpose of this application is to simplify attendance reporting for business owners or company managers, eliminating the need for manual attendance data recording, and making the attendance system of the company or factory more efficient.